2017
DOI: 10.1016/j.virusres.2017.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Community phytosanitation to manage cassava brown streak disease

Abstract: HighlightsThis study comprised the first attempt to manage cassava viruses with community phytosanitation for more than 70 years.Community phytosanitation resulted in area-wide reductions in CBSD incidence sustained over the 3-year duration of the study.Reduced CBSD and increased yields mean that community phytosanitation could be an important component of integrated cassava virus management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 27 publications
0
49
0
Order By: Relevance
“…Modelling has also shown that, to reduce CBSD dispersal and increase cassava yields, virus‐free planting material should be distributed to a number of different growers across a widespread area with restricted trade (McQuaid et al ., ). Once certified virus‐clean material has been distributed, farmers must also be thoroughly trained in the identification of disease symptoms to enable sufficient roguing to further reduce CBSD spread (Legg et al ., ; McQuaid et al ., ). Cassava clean seed system projects have recently been piloted in Uganda and Tanzania.…”
Section: Distribution Of Certified Virus‐clean Planting Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…Modelling has also shown that, to reduce CBSD dispersal and increase cassava yields, virus‐free planting material should be distributed to a number of different growers across a widespread area with restricted trade (McQuaid et al ., ). Once certified virus‐clean material has been distributed, farmers must also be thoroughly trained in the identification of disease symptoms to enable sufficient roguing to further reduce CBSD spread (Legg et al ., ; McQuaid et al ., ). Cassava clean seed system projects have recently been piloted in Uganda and Tanzania.…”
Section: Distribution Of Certified Virus‐clean Planting Materialsmentioning
confidence: 98%
“…Cassava clean seed system projects have recently been piloted in Uganda and Tanzania. (Legg et al ., ; McQuaid et al ., ).…”
Section: Distribution Of Certified Virus‐clean Planting Materialsmentioning
confidence: 98%
“…At 9 MAP, four plants per block were destructively harvested. Cross sections were made on the roots [33] to score severity of storage root necrosis (SRN) based on a 1-5 scale where 1no apparent necrosis and 5-root necrotic and severe constriction [31,32]. Non necrotic roots (score of 1.0) were counted as marketable storage roots (MSR) and their fresh weight weighed as marketable root yield (MRY) data.…”
Section: Field Experimentsmentioning
confidence: 99%
“…Positive selection for disease-free potato plants or plants with high (growth) vigor have shown to increase yields up to 34% [47]. Strategies focusing on resistant varieties have been reported for controlling CMD in Uganda [48], as elsewhere in SSA [49] but the use of healthy planting material has been advocated as the most easily applied control measure for CBSD [50,51]. Control measures for the management of pests and diseases in this region are varied and they include limiting the movement and use of infected planting materials, the use of pest/disease tolerant/resistant varieties such as "Cruza-148 (CIP 720118)" that is tolerant to potato late blight and bacterial wilt [52][53][54][55], as well as the routine monitoring/surveillance of the pest and disease distribution, incidence, and severity in farmers' fields by all stakeholders.…”
Section: Discussionmentioning
confidence: 99%